2009
DOI: 10.1109/tpel.2009.2023217
|View full text |Cite
|
Sign up to set email alerts
|

Power Distribution Based on Gyrators

Abstract: Basic configurations employed in the design of power architectures can be efficiently implemented by means of power gyrators. A modular architecture for a dc bus based on the connection of N g-gyrators and one r-gyrator is proposed to perform source splitting and achieve voltage regulation. Source splitting can provide high power, and it is implemented by paralleling the N output ports of the g-gyrators whose corresponding input ports are excited by independent voltage sources. Output voltage regulation is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In the case carried out in this article, the MPPT algorithm implemented has been the well-known perturb and observation (P&O) [5]. Notice that, for this tracking, it is necessary a second current and voltage sensing, in order to measure and introduce them to the PIC microcontroller.…”
Section: Component Design Of the Bif Power Gyratormentioning
confidence: 99%
“…In the case carried out in this article, the MPPT algorithm implemented has been the well-known perturb and observation (P&O) [5]. Notice that, for this tracking, it is necessary a second current and voltage sensing, in order to measure and introduce them to the PIC microcontroller.…”
Section: Component Design Of the Bif Power Gyratormentioning
confidence: 99%
“…2. The main antecedent of developing a power distributions system based on a single canonical element was reported in [31], where a dc grid was implemented using two different types of power gyrators, which were associated either in cascade or in parallel. A subsequent comparison between power gyrators and LFRs in the cascade connection of power converters in [28] revealed that LFRs exhibited a larger stability margin.…”
Section: Introductionmentioning
confidence: 99%
“…So, a high step-up dc-dc converter is usually used as a front-end converter for boosting the voltage with high efficiency and reliability. These requirements have led to various high step-up dc-dc converters proposed in the paper [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%